PENGARUH PENGGUNAAN APLIKASI SEGIEMPAT TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR - Irnawati; Andina Nurul Wahidah; Yumi Sarassanti (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
This research aims to find out 1) to detail the use of quadrilateral applications in learning flat shape mathematics for class VII students at SMPN 4 Batu Ampar; and 2) to prove the effect of using the quadrilateral application on mathematics learning outcomes regarding flat shapes in class VII students at SMPN 4 Batu Ampar. This research includes quantitative research with a quasi-experimental type of research. The population used was all class VII students at SMPN 4 Batu Ampar with a total of 47 people. The data collection techniques used in this research are (1) Test; (2) observation techniques; (3) documentation techniques. The data collection instruments used were (1) tests; (2) observation sheet; (3) documentation. The data analysis technique uses (1) prerequisite tests, namely the control class normality test sig (0.432) and the experimental class sig (0.833), then the homogeneity test sig (0.749); (2) hypothesis testing, namely the independent sample t-test sig (2-tailed) 0.001. The results of this research have answered all research objectives. Firstly, the use of the quadrilateral application in mathematics learning about flat shapes for class VII students at SMPN 4 Batu Ampar has 100% observation results in the use of the quadrilateral application. Second, there is an influence of using the quadrilateral application on the mathematics learning outcomes of flat shape material in class VII students at SMPN 4 Batu Ampar sig (0.001 ).